Reliability and Feasibility of Physical Fitness Tests in Female Fibromyalgia Patients - Carbonell-Baeza, A.; Álvarez-Gallardo, I. C.; Segura-Jiménez, V.; Castro-Piñero, J.; Ruiz, J. R.; Delgado-Fernández, M.; Aparicio, V. A. (International Journal of Sports Medicine, 2015)
The aim of the present study was to determine the reliability and feasibility of physical fitness tests in female fibromyalgia patients. 100 female fibromyalgia patients (aged 50.6±8.6 years) performed the following tests twice (7 days interval test–retest): chair sit and reach, back scratch, handgrip strength, arm curl, chair stand, 8 feet up and go, and 6-min walk. Significant differences between test and retest were found in the arm curl (mean difference: 1.25±2.16 repetitions, Cohen d=0.251), chair stand (0.99±1.7 repetitions, Cohen d=0.254) and 8 feet up and go (−0.38±1.09 s, Cohen d=0.111) tests. Intraclass correlation coefficients (ICC) range from 0.92 in the arm curl test to 0.96 in the back scratch test. The feasibility of the tests (patients able to complete the test) ranged from 89% in the arm curl test to 100% in the handgrip strength test. Therefore, the reliability and feasibility of the physical fitness tests examined is acceptable for female fibromyalgia patients.
Keywords: pain; muscle strength; flexibility; aerobic capacity; assessment